Laparo-therapy for abdominal tuberculosis: Case report with review of literature - Verma, Richa; Joshi, Abhijit Sharadchandra (Indian Journal of Case Reports, 2026)
Abdominal tuberculosis (TB) has many varied clinical presentations. It can vary from small bowel obstruction to peritoneal disease to lymphadenopathy to rare colonic TB to a combination of any or all of the above. Herein, the authors present the case of a 25-year-old female patient who had dense parietal adhesions of mesentery and small bowel loops and a large collection of pus in her lower abdomen. She had already been on anti-microbial therapy for 2.5 months for ascites. Investigations (imaging and laboratory) pointed toward worsening and increasing peritoneal collection. She underwent a successful laparoscopic adhesiolysis, drainage of the collection, along with excision of the wall and toilet. The first line anti-Koch’s medical therapy (which was already on since 2.5 months), as per culture report, was continued for 1 year. Subsequent surveillance imaging reports revealed no recurrence of the collection and, eventually, a complete cure.